Proceedings. Frontiers in Education. 36th Annual Conference 2006
DOI: 10.1109/fie.2006.322517
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a professional community of practice for graduate students in engineering education

Abstract: This paper examines the development of a professional community of practice among graduate students and faculty in the nation's first graduate program in engineering education. A cohort of eleven graduate students and four faculty were interviewed over the course of one year. Additional data sources included direct observations and review of supporting documents. Data were analyzed using grounded theory, narrative inquiry, and cross-case analysis. Results from this study: 1) provide a conceptual and structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The main goals of the program are to help each student to generate new knowledge, correctly apply their knowledge in problem solving, and to transform the new understandings through active and continued participation in the profession. The results showed that there is a deep connection between identity and participation in a professional community of practice [3].…”
Section: Introductionmentioning
confidence: 94%
“…The main goals of the program are to help each student to generate new knowledge, correctly apply their knowledge in problem solving, and to transform the new understandings through active and continued participation in the profession. The results showed that there is a deep connection between identity and participation in a professional community of practice [3].…”
Section: Introductionmentioning
confidence: 94%
“…Identity theory has been utilized to better understand students' choice to pursue fields in the STEM profession 18 , why they stay engaged through undergraduate and graduate programs 19,20 , as well as understanding the complexities of identity in the engineering workplace 7 . In science, identity theory has provided insight in to how minority women have redefined recognition in order to remain engaged and successful in a profession that has not been welcoming, historically 16 .…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Another topic featured in a large amount of engineering specific literature on graduate education is preparing engineering graduate students for their future careers (faculty versus industry) [39][40][41][42][43] or for positions they may hold during graduate school (teaching versus research assistant) [44][45][46][47][48][49] .…”
Section: Career Plans Of Engineering Graduate Studentsmentioning
confidence: 99%